Emotional and sensory profiling by children and teenagers: A case study of the check‐all‐that‐apply method on biscuits. Issue 1 (1st February 2017) - Schouteten, Joachim J.; De Steur, Hans; Lagast, Sofie; De Pelsmaeker, Sara; Gellynck, Xavier
Abstract: Sensory and emotional profiling by consumers is gathering interest among scientists and companies as it could help to better understand the motives for food choice. Although children and teenagers are important food consumer groups, they are underrepresented in sensory research and little is known on how children and teenagers perform on these tasks. Therefore, this study investigates the emotional and sensory profiling of a traditional biscuit product among 122 children and teenagers (10–14 years old). The check‐all‐that‐apply (CATA) approach has been applied for conducting the emotional and sensory profiling task using an age‐appropriate protocol. Children and teenagers evaluated four different samples (market leader, store brand, small producer, and local bakery) and assessed their overall liking under three conditions: blind, expected (brand logo) and informed. Overall liking differed significantly among the samples and brand information influenced the informed liking scores. Samples were associated with different emotional profiles and sensory attributes by the children and teenagers. Practical applications: This study illustrates the potential of using CATA questions for obtaining emotional connotations and sensory attributes of food products with children and teenagers. Together with the insights regarding their attitudes toward traditional food products and store brands, this could help producers when developing promotion initiatives to bring their traditional food products to a potential market of young consumers. Including both sensory and emotional measurements yield interesting insights for the product development if companies want to produce products in alignment with the brand message. Further, this study shows that branding influences not only the overall liking but also the sensory perception of the food products. Therefore, this study adds to the discussion on the need and importance of a more realistic product presentation during sensory testing.